Compositional Characterization of Native Peruvian Chili Peppers (Capsicum spp.) - Meckelmann, Sven W.; Riegel, Dieter W.; Van Zonneveld, Maarten J.; Ríos Lobo, Llermé; Peña Pineda, Karla Mónica; Ugás, Roberto; Quinonez, Lourdes; Mueller Seitz, Erika; Petz, Michael (American Chemical Society, 2020)
The national Capsicum germplasm bank of Peru at INIA holds a unique collection of more than 700 Capsicum accessions, including many landraces. These conserved accessions have never been thoroughly characterized or evaluated. Another smaller collection exists at UNALM, and CIDRA provided taxonomically characterized fruits from the Amazon region of Ucayali. Of these collections, 147 accessions have been selected to represent the biodiversity of Peruvian Capsicum annuum, Capsicum baccatum, Capsicum chinense, and Capsicum frutescens by morphological traits as well as by agronomic characteristics and regional origin. All fruits from the selected accessions have been oven-dried and ground in Peru and analyzed in Germany. Results are reported for each accession by total capsaicinoids and capsaicinoid pattern, total polyphenol content, antioxidant capacity, specific flavonoids (quercetin, kaempferol, luteolin, apigenin), fat content, vitamin C, surface color, and extractable color. A wide variability in phytochemical composition and concentration levels was found.